Monitoring abundance of pirarucu Arapaima gigas in the lower basin of Pacaya river, Pacaya Samiria National Reserve, Peruvian Amazon. - Torres Vasquez, Marìa Isabel (2017)
Information about the abundance of paiche Arapaima gigas in natural environment in the Peruvian Amazon is very scarce, being greater the results obtained from fisheries management programs through monitoring in places where they have been used for commercial purposes. This work shows the results of annual monitoring between 2014 and 2017 in the area of Yarina, Pacaya river basin, in the Pacaya Samiria National Reserve (PSNR), where the paiche population is not homogeneous in the bodies of water, registering higher average density in the Yarina and Huama watercourses compared to the Zapote and Yarina lakes. Likewise, the low depth of the bodies of water registered in the Huama watercourse during 2017, influence the abundance of the adult individuals of paiche, but not of the juveniles.